DINAMIKA INKLUSIVITAS DI PESANTREN: STUDI TENTANG MODAL BUDAYA DAN IDENTITAS SOSIAL - Ushansyah Ushansyah; Desi Erawati; Masdar Hilmy (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
This article is motivated by the need for pesantren to strengthen inclusive attitudes amid diverse student backgrounds and contemporary social dynamics that may foster exclusivity. It examines how cultural capital and social identity function as conceptual foundations for creating a more open and harmonious pesantren environment. Using a library research with a conceptual approach, this article draws on peer-reviewed journal articles, books, and relevant prior studies. Literature was collected through systematic searches using the keywords “cultural capital,” “social identity,” and “pesantren” in databases such as Scopus, Web Of Scene, Ebsco, Doaj, Google Scholar, with sources selected based on relevance and credibility. Data were analyzed through content analysis, including data reduction, thematic classification, interpretation of conceptual relationships, and the formulation of theoretical conclusions. The study proposes a comprehensive model explaining social dynamics and strategies for strengthening inclusivity in modern pesantren. Validity was ensured through careful source selection, theoretical triangulation, and verification of original texts. The findings indicate that pesantren values, norms, and traditions can foster solidarity when aligned with students’ social identity formation; however, misalignment may generate social distance and group dominance. Therefore, strengthening inclusivity requires character development, effective social interaction management, and the cultivation of an adaptive and moderate institutional culture.